Predictive mathematical model of time saved on descents in road cycling achieved through reduction in aerodynamic drag area - Drory, A.; Yanagisawa, M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2012)
This paper presents empirically-based simulation results of descent time to completion in road cycling. A mathematical model is formulated to predict time saved on road cycling descents where a cyclist`s position is static through manipulation of aerodynamic drag area, system parameters and initial conditions. Road cyclists often adopt drastic static riding positions on long descents in order to minimize aerodynamic drag and optimize performance, measured as race time to completion. In those riding positions bicycle control is compromised and the risk of fall and injury increases.